Pengaruh saluran distribusi, keunggulan produk, dan persediaan produk, melalui keputusan pembelian pada PT. Tasya Gasindo Medan - Munte, Annes; Jonathan Sibarani, Hendra (Jurnal Paradigma Ekonomika, 2021)
Natural gas is used by the public because it is more efficient and cheaper than others. but the 3 kg gas cylinder often leaks, the weight of the gas cylinder is not as expected, then the 3kg gas cylinder is often empty of stock. this study aims to determine the effect of distribution channels, product advantages, and product supplies through purchasing decisions. This type of research uses descriptive research. The research aims to determine the effect of distribution channels, product advantages, and product supplies through purchasing decisions. The population in the company as many as 70 and taken 30 populations from similar companies so that the population amounted to 100, the number of samples studied in this study were 100 samples. The study used multiple linear analysis shows distribution channels, product advantages, and product suppliesseffect spositive sand ssignificant sto purchasing sdecisions. The t-test of the distribution channel obtained tcount < ttable the sig value Fcount> Ftable means that the distribution channel has no effect and is not significant towards purchasing decisions, product excellence is obtained tcount > ttable then the sig value Fcount<Ftable means that product excellence has a significant effect on purchasing decisions, and value product inventory obtained tcount> ttable then the sig value Fcount < Ftable means that product inventory has a significant effect on purchasing decisions. Â